Nano-Molecular Junctions on STM Tips - Huang, Chun; Yang, Jianshu (Nano-Micro Letters, 2011)
We present a technique for metal-organic-metal junctions, which contain ten or fewer conjugated molecules between each of such junction, and the investigations of the I–V response of these junctions. The junctions are made by self assembling thiolated molecules onto gold coated tips for use in scanning tunneling microscopy. We show that this easy technique probes the qualitative properties of the molecules. Current-voltage characteristics of a Tour wire and a new molecular rectifier are presented.